(3GdEjVGMs - (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj, CHh Ydj,J (B377 (3g` s ((3Ydj Hf eMeO Hf Ydj Hf YHOGddg s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG Ydi CKQ Pdc CWGd Gddg HbGA Gdedc YVO GdOhdI s
(3BNQgG (B:s
(3hPdc Cf GdUGO hGdTjf GSJWGdJG MJi GJUdJG HeNGQL gPg GdMQha gPG BNQ cJGH GdEjVGM s
(3fSNI KGfjIs
(3de jPcQ aj YfhGfgG GdJcedIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGX HgG CKQ WeSs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs